Discourses of Ageing in Fiction and Feminism - King, J. author. aut Link
XVII, 221 p.
Keywords: This book explores the way older women are represented in society. Through close readings of novels by major 20th century novelists, compared with the more dominant representations of female ageing to be found in popular culture it suggests that they offer a feminist understanding of the 'invisible' woman sometimes lacking in feminism itself.